Molecular Surveillance of Carbapenem Resistant Acinetobacter baumannii (CRAB) from clinically significant Non fermenting GramNegative bacilli in a tertiary care hospital - Sureshkumar, Mathavi; Chandar, Sarath; C, Nalina (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Acinetobacter baumannii has emerged as a significant nosocomial pathogen, particularly in intensive care settings due to its remarkable ability to acquire resistance to multiple antimicrobial agents. Carbapenem-resistant Acinetobacter baumannii (CRAB) significantly limits therapeutic options and poses a serious clinical challenge. Molecular surveillance is essential to understand the distribution of resistance determinants and to guide infection control strategies. Objectives: To perform molecular surveillance of carbapenem-resistant A. baumannii isolated from clinically significant non-fermenting gram-negative bacilli (NFGNB) in a tertiary care hospital and to characterize the major carbapenem resistance genes. Methodology: A total of 196 clinically significant NFGNB isolates were collected from various clinical specimens over a defined study period. Acinetobacter baumannii were identified using conventional biochemical methods and confirmed by VITEK 2 automated system. Antimicrobial susceptibility testing was performed according to CLSI guidelines. Carbapenem resistance was defined based on resistance to imipenem and/or meropenem. Molecular detection of carbapenemase-encoding genes, including blaOXA-23, blaOXA-51, blaOXA-58, blaNDM and blaVIM was carried out using polymerase chain reaction (PCR). Results: Out of 196 NFGNB isolates, 39 isolates were A. baumannii, of which 31 (79.5%) were carbapenem resistant. Molecular analysis revealed the presence of intrinsic blaOXA-51 like gene in all carbapenem resistant A.baumannii isolates, with blaOXA-23 (74.2%) being the predominant acquired carbapenemase gene followed by blaNDM(19.3%) and a combination of blaOXA-58, blaNDM and blaVIM (6.5%). Conclusion: The study highlights the alarming burden of carbapenem resistance among A. baumannii isolates in the hospital setting. The predominance of blaOXA-23 underscores its major role in mediating resistance. Continuous molecular surveillance, strict infection control measures and robust antimicrobial stewardship programs are essential to curb the spread of CRAB and optimize patient management.